Effect of pueraria, scutellaria, and coptis decoction for type 2 diabetes: A systematic review and meta-analysis protocol - Yang, Maoyi (Medicine (Baltimore), 2020)
BACKGROUND: Type 2 diabetes mellitus is a common health problem in the world. The overall goal of diabetes management is to control blood glucose and lipids, so as to reduce the incidence of complications. Pueraria, scutellaria, and coptis decoction (PSCD) is 1 of the representative Traditional Chinese medicine formula in the treatment of diabetes, which is widely used in clinical practice in China. At present, there are many clinical reports about this formula, but these reports have their own defects. Therefore, there is an urgent need for a systematic review and meta-analysis to synthesize the current clinical evidence. METHODS AND ANALYSIS: A comprehensive literature search will be conducted and randomized controlled trials will be selected according to inclusion and exclusion criteria. Fasting blood glucose and 2 hours postprandial blood glucose will be selected as the main outcomes. The secondary outcomes are glycated hemoglobin, fasting insulin, total cholesterol, glycerol, low-density cholesterol, high-density cholesterol and adverse effects. Chi-square and I(2) test will be used to test the heterogeneity of the study. Subgroup analysis will be conducted to explore the source of heterogeneity and sensitivity will be conducted to test the stability of the results. Funnel plot will be used to evaluate publication bias. Finally, the Grading of Recommendations Assessment, Development and Evaluate system will be used to summarize the quality of evidence. RESULTS: The results will be published in peer-reviewed journals. CONCLUSION: This research will evaluate the efficacy of Pueraria, scutellaria, and coptis decoction in the treatment of type 2 diabetes mellitus patients. It will provide strong evidence-based support for clinical practice. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/WVDE5